Study of Phase Decomposition in ZrW2O81 . Issue 7 (29th March 2016) - Fedorova, Anna; Kämpf, Timo; Scheffler, Michael
Abstract : This paper describes the decomposition behavior of zirconium tungstate (ZrW2 O8 ) materials above 1 050 K. The materials are synthesized according to a sol–gel‐route and a solid‐state route, and have been characterized with respect to their crystallographic properties. Apart from the initial phase and decomposition products ZrO2 and WO3, the additional phase γ‐ZrW2 O8 is found, which results from a phase transition initiated by local pressures higher than 200 MPa. Residual stresses induced by the thermal mismatch between different phases within the composite material are found to be 1.15 GPa(ZrO2 /ZrW2 O8 ) and 1.26 GPa (WO3 /ZrW2 O8 ). Obtained stress values are high enough to induce this transition. Abstract : Thermal mismatch stresses between the initial phases ZrO2 and WO3 and the resulting ZrW2 O8 are evaluated. The obtained stress values are high enough to initiate the transformation into the γ‐ZrW2 O8 . The change of the phase composition with longer holding times above the decomposition temperature of the ZrW2 O8 shows remarkable differences depending on the used synthesis route (sol–gel or solid‐state).